Using Corrective Feedback to Enhance Oral Production (2023)
ABSTRACT : This action-research aimed at determining what happens when English learners are exposed to Corrective Feedback to enhance their oral production. It was conducted in a public school in Rionegro, Antioquia with a group of eight graders. Research actions included four strategies of Corrective Feedback; Recast, Repetition, Clarification Request and Explicit Correction involved in oral production activities. Data gathering instruments included research memos, student’s reflection, rubrics, and a focus group. Findings revealed that students resorted to writing before producing orally making definite the need for Explicit Correction, students required more than one Corrective Feedback strategy to improve Oral Production and students demanded more time than expected to prepare oral production activities.